THE IMPACT OF THE MILITARY EXPENDITURE AND SECURITY EXPENDITURE STRUCTURE ON THE SECURITY STABILITY - Saputro, Guntur Eko; Mahroza, Jonni; Tarigan, Herlina (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
The structure of defense spending in Indonesia State Budget consists of three types of spending, which are routine expenditure, goods expenditure, and capital expenditure. It shows the changes in consumption expenditure contribution, direct investment expenditure, and indirect investment from the government. According to The Global Competitiveness Report 2016-2017, Indonesia presents a low level of security stability among 138 countries. Due to the terrorism threat, Indonesia is ranked 115 (Global Competitive Index or GCI=4,2) for business cost, at the 102nd ranking (GCI=3,9) for the business cost caused by crime and violence, and 108th ranking (GCI=4,1) for organized crime. This study aims to examine the impact of military expenditure on security stability in Indonesia. The analytical method used in this study is explanatory, it aims to explain the causal relationship between variables and hypothesis testing. This study employs the time series data with per semester data series through 2000-2018. The research model is formulated as a recursive linear model in the form of a Cobb-Douglas production function and analyzed using multiple linear regression analysis with the Ordinary Least Square method. The result reveals that both military expenditure and security expenditure have impacted simultaneously on security stability. The integration of all components of military expenditure synergistically can increase Security Stability. The components of spending that have a partially significant positive effect on Security Stability are expenditures on goods and capital expenditures.